Spatial governance and planning systems in the public control of spatial development: a European typology. Issue 1 (2nd January 2021) - Berisha, Erblin; Cotella, Giancarlo; Janin Rivolin, Umberto; Solly, Alys
ABSTRACT: Although the functions of spatial governance and planning systems are generalizable, 30 years of comparative studies, especially in Europe, have shown the heterogeneity characterising these 'institutional technologies'. This contribution builds on the materials of the recently concluded ESPON COMPASS research project to propose a European typology on the capacity of public authorities to control spatial development, a crucial aspect for the life of entire cities, regions and countries. Based on the opinions expressed by respective national experts, the systems of 39 countries (28 EU and 11 non-EU) are compared in relation to the mechanisms to allocate land use and spatial development rights as well as to the prevalence of the state vs. the market in guiding the development decisions. As a result, the European systems are placed on an X-Y diagram, which makes it possible to cluster them in consistent types that raise new comparative observations and general findings. In summary, the capacity for public control of spatial development looks variegated in Europe, although limited overall. Even if the power relations between state and market established in each institutional context are certainly influential, the models adopted for allocating spatial development rights also play a role in determining the observed trends.